2019
DOI: 10.1371/journal.pone.0214769
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of sleep quality, smartphone dependence, and health-related behaviors in female junior college students

Abstract: Introduction Smartphone usage has become commonplace and impact on sleep quality among adolescents. Adolescent girls have a greater tendency toward sleep quality problems. However, relationship of sleep quality, smartphone dependence, and health-related behaviors in female junior college students has not been studied. Objectives This study had the two goals: to investigate the relationship between female college students' sleep quality, smartphone dependence, and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
82
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 53 publications
8
82
8
2
Order By: Relevance
“…Our ndings revealed that 12.2% of the participants rated themselves to have PSQ. Evidence from previous studies among adolescents, such as in the USA [5], Taiwan [7], Turkey, [29] and Nigeria [3,4] revealed higher rates, compared to the current report, which is higher than what was reported in India [30]. The disparity in rates may be related to the differences in research tools used to assess sleep quality, the de nition of terms, as well as the age of the participants.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Our ndings revealed that 12.2% of the participants rated themselves to have PSQ. Evidence from previous studies among adolescents, such as in the USA [5], Taiwan [7], Turkey, [29] and Nigeria [3,4] revealed higher rates, compared to the current report, which is higher than what was reported in India [30]. The disparity in rates may be related to the differences in research tools used to assess sleep quality, the de nition of terms, as well as the age of the participants.…”
Section: Discussioncontrasting
confidence: 80%
“…Sleep problems are common among children and adolescents in Nigeria [3,4] and beyond [5][6][7], and they are associated with physical and mental health indices. For example, while poor quality of sleep is associated with obesity, impaired blood lipids in adolescents [8], reduced learning capacity, and academic performance [9]; it is also associated with psychological symptoms such as depression, anxiety disorders, and behavioral disorders in studies among adolescents [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to investigate the relationship between sleep and IA. Some studies have reported an association between IA and depression and sleep disturbance [22,23], nighttime sleep duration and subjective insomnia [24], poor sleeping habits [25], smartphone dependence [26], and sleep quality [27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to investigate any relationships that exist between sleep and IA. Some studies have reported the relationship between IA and depression and sleep disturbance [22,23], nighttime sleep duration and subjective insomnia [24], poor sleeping habits [25], smartphone dependence [26], and sleep quality [27]. Sleeping habits are associated with other lifestyle habits, such as extracurricular activities and skipped meals [28,29].…”
Section: Introductionmentioning
confidence: 99%